Analisis Tanggung Jawab Perdata dalam Kebocoran Data: Sinkronisasi UU Perlindungan Data Pribadi dan KUH Perdata - Yanti, Musrika (Jurnal Ilmu Sosial dan Humaniora, 2025)
Personal data breaches in the digital era require synchronization between the Personal Data Protection Law and the Indonesian Civil Code to ensure effective civil liability and the protection of individual rights.This article aims to analyze the civil liability arising from personal data breaches, examine the existing disharmony between the UU PDP and KUHPer, and propose solutions for a more progressive and adaptive synchronization of civil law. The research method used is a normative approach with a juridical-comparative analysis. The study results indicate that while the UU PDP has regulated the right to compensation, the mechanisms and standards for proving claims remain ambiguous and heavily rely on the accountability system in KUHPer, which is less responsive to the dynamics of digital issues. These findings highlight the need for a reformulation of the legal framework to more effectively address the challenges of personal data protection.